The Extension of the Criminal Prosecution - Constantin Ioan Gliga (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
Criminal prosecution is the first, mandatory and essential, non-public, predominantly written and non-contradictory phase of the criminal proceedings, through which the criminal investigation bodies carry out pre-trial procedural activities. The extension of the criminal prosecution concerns the situation in which it is necessary to modify the procedural framework if, after gathering evidence, the criminal investigation bodies may discover that the person under investigation had committed several acts provided for by criminal law for which the in rem criminal prosecution was not initiated, or that the act under investigation had been committed by several persons who were not considered at the beginning of the investigation. The starting point of this paper is the presentation of the hypotheses, depending on the stage of the procedure in which the procedural framework is modified, as well as the issues that may arise in practice in situations where the prosecution authorities do not proceed with the extension of the criminal prosecution.